Computer-Based Cognitive Rehabilitation Interventions for Traumatic Brain Injury: A Critical Review of the Literature. - Fetta, Joseph; Starkweather, Angela; Gill, Jessica M. (Journal of Neuroscience Nursing, 2017)
Background: Computer-based interventions have been developed to improve cognitive performance after mild traumatic brain injury; however, a thorough evaluation of this body of research has not been addressed in the literature. Objectives: The aim of this study was to provide a synthesis and critical review of current research studies that have tested the efficacy of computer-based interventions on cognitive performance after mild traumatic brain injury. Methods: A critical review was conducted by identifying relevant studies in the electronic databases PubMed/MEDLINE, PsycInfo, and CINAHL from 2011 to the present. Because of the limited number of publications focused exclusively on mild traumatic brain injury, research studies that assessed the impact of computer-based interventions on cognitive outcomes in populations with acquired brain injury were included. Results: Of the 58 studies identified, only 10 publications included participants with mild traumatic brain injury. Overall, the identified studies did not use a standard method for assessing the severity of traumatic brain injury, and many studies included participants with a wide variety of etiologies for acquired brain injury and used multiple measures of cognitive performance, which made comparisons difficult across studies. In addition to small sample sizes, the study samples were heterogeneous in regard to the number of previous traumatic brain injuries, time elapsed since injury, and age and gender distributions. Preinjury comorbidities that may affect cognitive performance, such as depression, anxiety, or learning disabilities, were often not assessed. Discussion: There is weak evidence that computer-based interventions can improve working memory and cognitive function in individuals after mild traumatic brain injury. Because of the low-quality evidence, seminal questions remain regarding the optimal format, dosage, timing, and duration of computer-based intervention for improving cognitive performance. Future studies should focus on using a strong research design, such as a prospective, longitudinal, repeated-measures study, with an adequate number of participants who meet mild traumatic brain injury criteria. Preinjury comorbidities, cognitive reserve, time since injury, age, and gender should be addressed in the design because there may be differences in recovery time and mechanisms of cognitive plasticity among populations. Conclusions: Overall, computer-based interventions seem promising as an approach to improve working memory in individuals with acquired brain injury. There is no evidence that currently available interventions are specific to mild traumatic brain injury. Well-designed research studies with adequate sample sizes are needed to assess the effect of computer-based interventions on cognitive performance after mild traumatic brain injury.